Sistem Administrasi Klinik Sehat Abadi Kota Bekasi - Ade Kurnia Solihin; Galuh Krisna Dewanti (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2024)
The purpose of this research is to design a clinical administration application system at the Anugerah Clinic, so that administrative data processing at the Grace Clinic is easier and more systematic, so that reporting is more accurate and structured. The research methodology used in the data processing system is data collection techniques such as observing documentation studies, as well as conducting literature research that is relevant to information system problems. The system development method used uses grounded research methods.